Neo-tropical species production: a sustainable strategy for climate change adaptation in neo-tropical regions - Laura Tardieu; Marc A. Driscoll; Kegan R. Jones (BMC Veterinary Research)
Abstract This opinion piece clarifies the impact of climate change on animal production in the Latin America and Caribbean (LAC) region and proposes a sustainable solution. Anthropogenic climate change has resulted in higher ambient temperatures, rainfall, humidity, storms and desertification. These events have direct and indirect effects on conventional animal performance and this piece will highlight the impact of increased temperatures on their welfare, health and production in the LAC. Alternative species such as neo-tropical wildlife animals have been proposed as climate resilient animals for use in the LAC, as they are well adapted to the climate and environment in the tropics. Some of these animals include capybara, lappe, agouti, caiman, cocrico and collared peccary. Neo-tropical animal production has the potential to produce nutritious meat, quality leather, reduce pollution and serve as a form of sustainable production. These animals can be inserted into a sustainable production system as their feed resources can be supplied through the use of local feedstuff, they also require less water and energy for maintenance, as they are well adapted to the high temperature and humidity in comparison to domesticated animals such as cattle, pigs and chickens. Finally, the key challenges including the legal use of the animals throughout the year, lack of technical experience and limited knowledge on the biology of these animals are discussed.